Whole-Body Electromyostimulation Training for Body Composition, Muscle Strength, and General Health Outcomes: A Brief Review of the Benefits and Side Effects - De Camargo, Jlio Benvenutti Bueno; Volpi Braz, Tiago; Kemmler, Wolfgang; Lopes Evangelista, Alexandre; Sales Bocalini, Danilo (Strength and Conditioning Journal, 2024)
Whole-body electromyostimulation training (WB-EMS) has gained increasing popularity as a training method in recent years. This brief review aims to summarize the potential benefits and risks of WB-EMS in many different populations and purposes. The findings of this review suggest that WB-EMS is particularly effective for improving muscle mass and strength outcomes in untrained people. However, more high-quality studies are needed to determine its long-term effects and to optimize its use in different populations and training contexts. For general health-related parameters, WB-EMS may be a feasible and time-efficient exercise strategy combined with proper energy or protein intake throughout longer periods.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electrical; exercise; prescription; training